The Correlation Between the Use of Eyeglasses and Gender with Computer Vision Syndrome Symptoms - Sawitri, Endang; Apriyanti, Sofia (Technium BioChemMed, 2024)
Background: Computer Vision Syndrome (CVS) is a group of symptoms related to eye and vision problems caused by long-term use of computers, tablets, smartphones, and other electronic devices. Several risk factors of CVS have been identified, including individual factors, such as gender and the use of eyeglasses. Objectives: Therefore, this study aimed to determine the correlation between the use of eyeglasses and gender with CVS symptoms among students at the Faculty of Medicine, Mulawarman University, Samarinda. Methods: The study procedures were carried out using an observational analytic method with a cross-sectional design. The sample population comprised 177 students from the Medicine, Dental, and D-3 Nursery Study Programs. Data were then obtained using the Computer Vision Syndrome Questionnaire (CVS-Q) with the assistance of Google Forms and analyzed with the Chi-Square test. Result and Conclusion: The results showed that a total of 146 students (82.5%) experienced CVS symptoms. In addition, the results of statistical tests revealed that risk factors, such as the use of eyeglasses (p= 0.019 OR= 2.990) and gender (p = 0.005 OR = 3.183) had a significant association with CVS symptoms.